Resolving the Hadith Contradictions According to Ibn Qayyim Al-Jawziyyah - Fitah Jamaludin; Aminullah Elhady; Kasman Kasman (Universitas Darussalam Gontor, 2025)
This study examines the methods of resolving hadith discrepancies proposed by Ibn Qayyim al-Jawziyyah. The issue of hadith contradiction (ikhtilaf al-hadith) often causes understanding the Prophet's guidance (peace be upon him). Ibn Qayyim adopted a systematic approach to harmonize seemingly contradictory hadiths through the methods of reconciliation (al-jamʿ), abrogation (nasakh), and preference (tarjih). This research employs a qualitative-descriptive approach based on library research. The findings reveal that the method of reconciliation (al-jamʿ) is predominantly used by Ibn Qayyim, taking into account the strength of the transmission chains (sanad), historical context, and the principles of maqasid al-shariʿah. This study highlights Ibn Qayyim’s significant contribution to preserving the coherence of hadith understanding and its relevance to the dynamics of contemporary Islamic law.